Trade liberalization, agriculture, and poverty in low-income countries - Kym Anderson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper offers an economic assessment of the opportunities and challenges provided by the WTO's Doha Development Agenda, particularly through agricultural trade liberalization, for low-income countries seeking to trade their way out of poverty. After discussing links between poverty, economic growth and trade, it reports modelling results showing that farm product markets remain the most costly of all goods market distortions in world trade. It focuses on what such reform might mean for countries of South Asia and sub-Saharan Africa in particular, both without and with their involvement in the MTN reform process. What becomes clear is that if those countries want to maximize their benefits from the Doha round, they need also to free up their own domestic product and factor markets so their farmers are better able to take advantage of new market-opening opportunities abroad. Other concerns of low-income countries about farm trade reform also are addressed: whether there would be losses associated with tariff preference erosion, whether food-importing countries would suffer from higher food prices in international markets, whether China's WTO accession will provide an example of trade reform aggravating poverty via cuts to prices received by Chinese farmers, and the impact on food security and poverty alleviation. The paper concludes with lessons of relevance for low-income countries for their own domestic and trade policies. – WTO ; agricultural protection ; trade liberalization ; poverty alleviation
Keywords: F13; F15; F17; Q17; 330; Außenhandelsliberalisierung; Agrarprotektionismus; Armut; Low-Income Countries